IMPACT OF PLAY ON PRESCHOOL CHILD DEVELOPMENT - Rahmonova Gulchehraxon Tojnazarovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the topic of the impact of the game on the development of a child of preschool age. Also in the text of the article, the content of some research on the scientific and methodological foundations of the development of cognitive processes in children of preschool age through play activity is widely covered.